A LITERATURE REVIEW: URBAN TEENAGERS' READINESS TO IMPROVE THE QUALITY OF LIFE TOWARD THE MENARCHE - Anita Setyawati; Restuning Widiasih; Ermiati E; Ida Maryati (Journal of Maternity Care and Reproductive Health, 2019)
Menarche is the first experience of menstruation would cause anxiety among teenagers, fear, discomfort, and affect the quality of life of teenage. This condition was caused by the taboo assumption to discuss menstruation with family and their environment. Therefore, this study was conducted to identify urban teenagers' readiness toward menarche. This study was conducted with the process of searching, collecting and analyzing articles. The search sources used were Cinahl, Scopus, Cochrane, Pubmed, and Cengage databases. The keywords used were menarche, readiness, and urban teenagers. The inclusion criteria used were 2013 - 2018 research articles, full text, and English articles. The exclusion criteria used was non-urban teenagers. According to the keyword was found 124 articles. After being selected based on the inclusion and exclusion criteria, 7 articles were analyzed. The result showed urban teenagers' readiness consisted of internal and external readiness. Internal readiness consists of age and knowledge. Internal readiness can affect self-acceptance, maturity of mind, and views on the stages of growth and development that are being faced. External readiness consists of social support. Social support for urban teenagers is useful to get information and attention when menarche. External readiness for urban teenagers was already good but lack of internal readiness. Therefore, counseling and health education related to menarche was needed starting from elementary school.Keywords: Menarche, readiness, urban teenager.